NATIONAL HERITAGE POTENTIAL SITE: EMPHASIZING THE IMPORTANCE OF HISTORIC CORE SPATIAL AREAS IN KOTA KINABALU - Misni, Alamah; Funk, Eric Gabriel; Kamaruddin, Siti Mazwin; Halil, Faridah Muhamad (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2025)
Heritage symbolizes the community of a place and provides its residents with a sense of identity, belonging, and pride. The historical cores of cities, where many important buildings are located, play a crucial role in shaping a city’s identity. However, these historical cores and their built heritage are often threatened by modern development, leading to a loss of identity. The historical core of Kota Kinabalu, the capital of the Malaysian state of Sabah, is no exception to this unfortunate trend. To evaluate the significance of the historic core sites in Kota Kinabalu, site observations and expert interviews were conducted in both semi-structured and open-ended formats. The assessment was based on six indicators of significance: building typology, historical importance, social and cultural associations, aesthetic value, information value, and the richness, diversity, or unusual integration of features. These indicators were derived from the criteria outlined in Section 67 of the National Heritage Act of 2005. The analysis of the interviews was done using ATLAS.ti software, and the qualitative data were presented in graphic forms. While all six indicators were generally considered relevant, some experts disagreed regarding the suitability of building typology, aesthetic value, and informational value for the historic core of Kota Kinabalu. This study findings demonstrate that the historic core of Kota Kinabalu deserves designation as a National Heritage site. Furthermore, it encourages other Malaysian cities to utilize the same indicators to advocate for the preservation of their own historic cores.